2012
DOI: 10.3390/molecules170910791
|View full text |Cite
|
Sign up to set email alerts
|

Mesua beccariana (Clusiaceae), A Source of Potential Anti-cancer Lead Compounds in Drug Discovery

Abstract: An investigation on biologically active secondary metabolites from the stem bark of Mesua beccariana was carried out. A new cyclodione, mesuadione (1), along with several known constituents which are beccamarin (2), 2,5-dihydroxy-1,3,4-trimethoxy anthraquinone (3), 4-methoxy-1,3,5-trihydroxyanthraquinone (4), betulinic acid (5) and stigmasterol (6) were obtained from this ongoing research. Structures of these compounds were elucidated by extensive spectroscopic methods, including 1D and 2D-NMR, GC-MS, IR and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The structure-activity relationship (SAR) study revealed that the diprenyl, dipyrano, and prenylated pyrano substituent groups of the xanthone derivatives contributed towards the cytotoxicities [22]. Moreover, preliminary tests of cytotoxicity on other isolated metabolites were also reported [9, 21]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure-activity relationship (SAR) study revealed that the diprenyl, dipyrano, and prenylated pyrano substituent groups of the xanthone derivatives contributed towards the cytotoxicities [22]. Moreover, preliminary tests of cytotoxicity on other isolated metabolites were also reported [9, 21]. …”
Section: Resultsmentioning
confidence: 99%
“…Recent pharmacognosy analysis on Mesua ferrea leaf and fruit extracts showed both methanolic extracts to exhibit good antibacterial activity towards Staphylococcus aureus [11]. Previous research papers on Mesua species have shown that these plants exhibit many biological activities such as antioxidant [12–14], hepatoprotective [12], antiarthritic [15], immunomodulatory [16], antibacterial [17], antiacetylcholinesterase (AChE) [18], and larvicidal [19] activities, as well as antiproliferative effects [9, 2022]. These plants were thus selected for our pharmacological investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Even this compound exhibited strong inhibition of cell proliferation, indicating its effectiveness as another anti-cancer lead compounds from the same plant (Teh et al, 2012). In another study, the crude hexane extract of the vines of B. Strychnifolia have also been found to be highly cytotoxic (IC 50 value of 1.86 μg/ml) in KB3-1 (Kaewpiboon et al, 2012).…”
Section: Hexane Extractsmentioning
confidence: 94%
“…Stigmasterol exhibited strong inhibition of cell proliferation, an indication of its effectiveness as anticancer lead compounds (Teh et al, 2012).…”
Section: Dichloromethane Extractsmentioning
confidence: 99%
“…Motivated by the prospect of finding new α-glucosidase inhibitors from this extract, we have embarked on the isolation of the phytochemicals utilizing modern chromatographic techniques. Herein, we report the isolation and structural elucidation of six new isomeric polycyclic polyprenylated acylphloroglucinols (PPAPs) named mesuaferroic acid A, B, C, E and F (1)(2)(3)(4)(5) and their α-glucosidase inhibitory activity.…”
mentioning
confidence: 99%